AZF1 Is a Glucose-Dependent Positive Regulator of CLN3 Transcription in Saccharomyces cerevisiae - Newcomb, Laura L. (American Society for Microbiology, 2002)
Transcription of the CLN3 G(1) cyclin in Saccharomyces cerevisiae is positively regulated by glucose in a process that involves a set of DNA elements with the sequence AAGAAAAA (A(2)GA(5)). To identify proteins that interact with these elements, we used a 1-hybrid approach, which yielded a nuclear zinc finger protein previously identified as Azf1. Gel shift and chromatin immunoprecipitation experiments show that Azf1 binds to the A(2)GA(5) CLN3 regulatory sequences in vitro and in vivo, thus identifying a transcriptional regulatory protein for CLN3 and a DNA sequence target for Azf1. We show that glucose-induced expression of a reporter gene driven by the A(2)GA(5) CLN3 regulatory sequences is dependent upon the presence of AZF1. Furthermore, deletion of AZF1 markedly reduces the transcriptional induction of CLN3 by glucose. In addition, Azf1 can induce reporter expression in a glucose-specific manner when artificially tethered to a promoter via the DNA-binding domain from Gal4. We conclude that AZF1 is a glucose-dependent transcription factor that interacts with the CLN3 A(2)GA(5) repeats to play a positive role in the regulation of CLN3 mRNA expression by glucose.